Tamoya haplonema (Cnidaria: Cubozoa) from Uruguayan and adjacent waters: Oceanographic context of new and historical findings - Leoni, Valentina; González, Silvana; Ortega, Leonardo; Scarabino, Fabrizio; Siquier, Gabriela Failla; Dutra, Alicia; Rubio, Luis; Abreu, Martin; Serra, Wilson; Campi, Ana Gabriella Alonzo; Stampar, Sergio N. [UNESP]; Morandini, André C. (Springer Nature, 2016)
New records of the cubozoan jellyfish Tamoya haplonema in Uruguayan waters are reported together with historical records for the region, and associated with the oceanographic conditions at the moment of the finding. Occurrences of the species are mainly associated with positive Sea Surface Temperature Anomalies especially during summer months when the intrusion of warm oceanic waters to the Uruguayan coastline is stronger. This was particularly strong during 2012-2013, when a dry period enhanced this scenario. This species is the only cubozoan present in Uruguay, with a sporadic occurrence and so far has no appreciated negative effects on public health. However, from observed increasing frequency of positive temperature anomalies it would be reasonable to predict a future southward shift in the latitudinal distribution of T. haplonema. In this context, occurrence of this toxic species along Uruguayan coastal waters must be considered with particular attention to the potential negative impact on tourism and on general public health.
Keywords: Box jellyfish; South Atlantic; Tamoya haplonema; Uruguay